Knowledge and death penalty opinion: a test of the Marshall hypotheses - Bohm, Robert M. (Journal of research in crime and delinquency, 1991)
Three hypotheses about death penalty opinion derived from conjectures made by Justice Marshall in his Furman decision were tested. Findings of the study provide at least qualified support for all three hypotheses. Regarding the first and third hypotheses, subjects generally lacked knowledge about the death penalty and its effects prior to exposure to an experimental stimulus, and, to the degree that retribution provided the basis for support, knowledge had little effect on changing death penalty opinions. The second hypothesis, that an informed public would generally oppose the death penalty, was supported in some tests but not in others. Implications of the findings are discussed